Development and Evaluation of a Navigation-Based, Multilevel Intervention to Improve the Delivery of Timely, Guideline-Adherent Adjuvant Therapy for Patients With Head and Neck Cancer. Issue 10 (October 2021) - Graboyes, Evan M.; Sterba, Katherine R.; Li, Hong; Warren, Graham W.; Alberg, Anthony J.; Calhoun, Elizabeth A.; Nussenbaum, Brian; McCay, Jessica; Marsh, Courtney H.; Osazuwa-Peters, Nosayaba; Neskey, David M.; Kaczmar, John M.; et al.
Abstract : PURPOSE: More than half of patients with head and neck squamous cell carcinoma (HNSCC) experience a delay initiating guideline-adherent postoperative radiation therapy (PORT), contributing to excess mortality and racial disparities in survival. However, interventions to improve the delivery of timely, equitable PORT among patients with HNSCC are lacking. This study (1) describes the development of NDURE (Navigation for Disparities and Untimely Radiation thErapy), a navigation-based multilevel intervention (MLI) to improve guideline-adherent PORT and (2) evaluates its feasibility, acceptability, and preliminary efficacy. METHODS: NDURE was developed using the six steps of intervention mapping (IM). Subsequently, NDURE was evaluated by enrolling consecutive patients with locally advanced HNSCC undergoing surgery and PORT (n = 15) into a single-arm clinical trial with a mixed-methods approach to process evaluation. RESULTS: NDURE is a navigation-based MLI targeting barriers to timely, guideline-adherent PORT at the patient, healthcare team, and organizational levels. NDURE is delivered via three in-person navigation sessions anchored to case identification and surgical care transitions. Intervention components include the following: (1) patient education, (2) travel support, (3) a standardized process for initiating the discussion of expectations for PORT, (4) PORT care plans, (5) referral tracking and follow-up, and (6) organizational restructuring. NDURE was feasible, as judged by accrual (88% of eligible patients [100% Blacks] enrolled) and dropout (n = 0). One hundred percent of patients reported moderate or strong agreement that NDURE helped solve challenges starting PORT; 86% were highly likely to recommend NDURE. The rate of timely, guideline-adherent PORT was 86% overall and 100% for Black patients. CONCLUSION: NDURE is a navigation-based MLI that is feasible, is acceptable, and has the potential to improve the timely, equitable, guideline-adherent PORT.